Telaah Epistemologis Harmonisasi Sufisme dan Surealisme dalam Perspektif Adonis - Asmara Edo Kusuma (Fakultas Ushuluddin, Adab dan Humaniora (FUAH) UIN Kiai Haji Achmad Siddiq Jember, 2018)
This article explores the idea of mysticism promulgated by Adonis. To him, his works are an attempt to arrive at the disclosure of the visible and the hidden (al-kashf ‘an al-mar’ wa al-lā mar’ī). He acknowledges that the effort is based on the concept of ẓāhir and bāṭin within Sufism. The element of mysticism in Adonis’s idea has been manifested through the harmonization of Sufism-Surrealism. He uses other perspectives in defining Sufism and Surrealism; a perspective that enables the harmonization of both. To investigate the harmonization, the author employs epistemological point of view coupled with phenomenological approach as the methods of analysis of Adonis’s texts. The study reveals another type of Sufism and Surrealism, which emanates from the world of Adonis. Adonis has understood Sufism and Surrealism as two separate realms but they share one similar purpose, namely being identical with the Absolute or united with Him. Most radically, he views Sufism as a non-religious school, instead a universal philosophy of life to understanding the Universe. On the other hand, Adonis sees Surrealism as another form of mysticism, i.e. mysticism with no religious institution;